Sulfate resistance of mortars containing silica fume and pozzolan - Canpolat, Fethullah (ICE PUBLISHING, 2012)
An investigation was carried out on the effect of sulfate attack on the sulfate durability of mortars produced with natural zeolite and silica fume having pozzolanic character. Experiments were conducted on the standard RILEM-sand and Portland cement mortars where the cement was replaced by various rates of natural zeolite and silica fume separately and together. Five percent sodium sulfate solution and 5% magnesium sulfate solution were used for sulfate exposures of mortars, after 28 days of lime-saturated water curing. Compressive strength and density were determined at the beginning of exposure and at the 2nd, 7th, 28th, and 90th days. Water and sulfate solutions were renewed after each period of experimental time at 14 days. Mass changes were determined at the time of renewing the solutions. The effects of sodium sulfate solutions on the properties of mortars were studied due to the zeolite and silica fume ratio. It was found that zeolite and silica fume replacement had caused significant increase in sulfate durability of mortars even at the highest sulfate or magnesium or both sulfate concentration up to 90 days of exposure. The test results showed that the use of zeolite and silica fume in concrete exposed to the magnesium sulfate environment is not recommended.
Keywords: concrete technology & manufacture; energy conservation; recycling & reuse of materials; Construction & Building Technology